Low-Temperature Bleaching of Cotton Cellulose using an Ultrasound-assisted Tetraacetylethylenediamine/ Hydrogen Peroxide/Triethanolamine System - Abdulaziz A. Alghamdi; Essam S. Abdel-Halim; Zeid A. Al-Othman (BioResources, 2016)
This work investigated the efficiency of a tetraacetylethylenediamine/ hydrogen peroxide/triethanolamine (TAED/H2O2/TEA) system for low-temperature bleaching of cotton fabric, with and without ultrasonic assistance. The low-temperature bleaching results were compared to those obtained from a conventional H2O2 bleaching system. The application of TAED/H2O2/TEA without ultrasonic assistance to grey cotton fabric with a whiteness index (WI) of 28 and tenacity of 40 CN/Tex resulted in full bleaching of the cotton fabric at 70 °C within 60 min. This low-temperature bleaching system produced a bleached cotton fabric with a WI of 69 and tenacity of 38 CN/Tex, while the conventional H2O2 bleaching system gave a bleached cotton fabric WI of 73 and tenacity of 32 CN/Tex. The application of ultrasound to a low-temperature bleaching system showed a reduction in the duration required for full bleaching to 30 min rather than 60 min and gave bleached fabrics of the same physiochemical properties.